IMPLEMENTASI METODE AHP DAN TOPSIS DALAM ANALISIS MINAT ALUMNI BERDASARKAN PENILAIAN SERAPAN ALUMNI - Matahari (POLITEKNIK PIKSI GANESHA, 2020)
Preparation of curriculum and education program at vocational high school is conducted within five years with evaluation every year, and then adjusted to the needs of industry in the area around the school. The absorption of alumni in the industry can affect the determination of curriculum and education program, the evaluation done by looking up alumni annually determines the next step that vocational high school will be taken in preparing curriculum and educarion program. In addition, alumni absorption can show the quality of vocational high school from the quantity of alumni entering the industry world. For now the absorption data of alumni has not been used optimally, with an objective assessment. Therefore, further research is needed in assessing the absorption of alumni after graduation by tracing the interest of alumni in looking for work. This research uses Analytical Hierarchy Process (AHP) method and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in tracing the interest of alumni in finding work by knowing the factors that influencing the interest of alumni in industry. By using data of alumni absorption and interview of vocational high school stakeholder, it was found that AHP method can be used in weighting criteria as well as alternative and TOPSIS method as comparison and consideration of the selection of the best alternative. This research had result that combination of AHP and TOPSIS can give the best alternative recommendation. The results that obtained by using AHP and TOPSIS is found that the alternative of private companies is the best choice that alumni is interest in it.